NIMG-36. EVALUATION OF [18F]DASA-23 FOR NON-INVASIVE MEASUREMENT OF ABERRANTLY EXPRESSED PYRUVATE KINASE M2 IN GLIOMA: FIRST-IN-HUMAN STUDY. (11th November 2019) - Patel, Chirag; Beinat, Corinne; Haywood, Tom; Murty, Surya; Xie, Yuanyang; Recht, Lawrence; Nagpal, Seema; Thomas, Reena; Khalighi, Mohammad; Gandhi, Harsh; Holley, Dawn; Gambhir, Sanjiv
Abstract: OBJECTIVES: We developed 1-((2-fluoro-6-(fluoro-[18F])phenyl)sulfonyl)-4-((4-methoxyphenyl)sulfonyl)piperazine ([18F]DASA-23) as a novel radiopharmaceutical to measure pyruvate kinase M2 levels by positron emission tomography (PET). PKM2 catalyzes the final step in glycolysis, the key process of tumor metabolism. PKM2 is preferentially expressed by glioblastoma (GBM) cells with minimal expression in the healthy brain, making it an important biomarker of cancer glycolytic re-programming. Here, we report the first evaluation of [18F]DASA-23 in human healthy volunteers and subjects with low-grade (LGG) and high-grade glioma (HGG). METHODS: [18F]DASA-23 was synthesized under GMP conditions. Brain [18F]DASA-23 PET/MRI scans (3T) were performed in human healthy volunteers (n=5) and subjects with LGG (n=3) and HGG (n=2). The PET imaging duration was 60 min and standardized uptake value (SUV) calculations were performed on the 30–60 min summed images. The maximum SUV in the tumor (TumorSUVmax) and contralateral white matter (WMSUVmax) were calculated. RESULTS: [18F]DASA-23 specific activity was 2961±873 mCi/µmol (n=10) with radiochemical purity >95%, injected mass of 1.8±0.7 mcg, and dose of 0.3±0.02 mcg per kg body weight. In healthy volunteers, [18F]DASA-23 crossed the intact blood-brain barrier and was rapidly cleared through the bladder and also showed uptake in the gallbladder, liver, and intestines over time. [18F]DASA-23 was found to be intact in plasma up to 10 min post-injection and 75% intact at 30 min post-injection. In subjects with glioma, TumorSUVmax was significantly greater in HGG (2.2±0.4, n=2) compared to LGG (0.8±0.3m n=3), p=0.02. In this early human series, the normalized ratio of TumorSUVmax/WMSUVmax was not significantly different between subjects with HGG (2.0±0.6) and LGG (1.0±0.4), p=0.1. CONCLUSION: [18F]DASA-23 is a promising new imaging agent for the non-invasive delineation of LGG and HGG based on aberrantly expressed PKM2. An ongoing study is evaluating the utility of this agent in additional patients with intracranial malignancies (NCT03539731).